HISTOLOGICAL STRUCTURE AND CHARACTERISTICS OF THE THYROID GLAND (Multidisciplinary Journal of Science and Technology, 2026)
This article discusses the histology, shape, and sex-specific characteristics of the thyroid gland. The thyroid gland is a butterfly-shaped, important endocrine gland located in the lower neck. It is located anteriorly and laterally to the trachea, below the larynx. In addition to playing an important role in calcium metabolism, it also plays an important role in regulating basal metabolic rate (BMR) and stimulating somatic and mental growth.